Macrophage Depletion Lowered Blood Pressure and Attenuated Hypertensive Renal Injury and Fibrosis - Huang, Lei; Wang, Aimei; Hao, Yun; Li, Weihong; Liu, Chang; Yang, Zhihang; Zheng, Feng; Zhou, Ming-Sheng (Frontiers in Physiology, 2018)
Monocyte/macrophage recruitment is closely associated with the degree of hypertensive renal injury. We investigated the direct role of macrophages using Liposome encapsulated clodronate (LEC) to deplete monocytes/macrophages in hypertensive renal injury. C57BL/6 mice were treated with a pressor dose of angiotensin (Ang, 1.4 mg/kg/day) II plus LEC or the PBS-liposome for two weeks. Ang II mice developed hypertension, albuminuria, glomerulosclerosis and renal fibrosis. LEC treatment reduced systolic blood pressure (SBP), albuminuria and protected against renal structural injury in Ang II mice. Ang II significantly increased renal macrophage infiltration (MOMA2+ cells) and the expression of renal tumor necrosis factor  and interleukin1, which were significantly reduced in Ang II/LEC mice. Ang II increased renal oxidative stress and the expression of profibrotic factors transforming growth factor (TGF)  and fibronectin. Ang II also inhibited the phosphorylation of endothelial nitric oxide synthase (phoshpho-eNOS, ser1177). LEC treatment reduced renal oxidative stress and TGF1 and fibronectin expressions, and increased phospho-eNOS expression in the Ang II mice. In Dahl rats of salt-sensitive hypertension, LEC treatment for 4 weeks significantly attenuated the elevation of SBP induced by high salt intake and protected against renal injury and fibrosis. Our results demonstrate that renal macrophages play a critical role in the development of hypertension and hypertensive renal injury and fibrosis; the underlying mechanisms may be involved in the reduction in macrophage-driven renal inflammation and restoration of the balance between renal oxidative stress and eNOS. Therefore, macrophages should be considered as a potential therapeutic target to reduce the adverse consequences of hypertensive renal diseases.